2023
DOI: 10.3389/fpsyt.2023.1114725
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic injustice and mental health research: A pragmatic approach to working with lived experience expertise

Abstract: “Epistemic injustice” refers to how people from marginalized groups are denied opportunities to create knowledge and derive meaning from their experiences. In the mental health field, epistemic injustice occurs in both research and service delivery systems and particularly impacts people from racialized communities. Lived experience involvement and leadership are often proposed as methods of combatting epistemic injustice, a tool for ensuring the views of people at the center of an issue are heard and can info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…We noted in the introduction that the issue of meaning being lost in translation within research efforts has been identified in our recent narrative review and synthesis of the priorities for mental health research and translation over the past twelve years [1]. This loss of meaning is an example of the epistemic injustice that is common in mental health care and research [9,23]. Part of the threat to the salient meanings of those most impacted lies in efforts of large-scale studies [e.g., 4, 5, 8] to reach consensus both within and across various groups with interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We noted in the introduction that the issue of meaning being lost in translation within research efforts has been identified in our recent narrative review and synthesis of the priorities for mental health research and translation over the past twelve years [1]. This loss of meaning is an example of the epistemic injustice that is common in mental health care and research [9,23]. Part of the threat to the salient meanings of those most impacted lies in efforts of large-scale studies [e.g., 4, 5, 8] to reach consensus both within and across various groups with interest.…”
Section: Discussionmentioning
confidence: 99%
“…focus on consensus carries the risk that genuinely diverse views and complex meaning are lost, and trying to achieve this across groups with unequal power in priority-setting will silence some voices, favouring clinical, academic and professional knowledge over lived experience [9,23]. This risk is acknowledged in these other priority-setting studies, with explicit efforts to elevate lived experience voices amongst the many.…”
Section: Plos Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is no standard methodology, a community-engaged research agenda-setting process commits to giving community stakeholders an equal role in knowledge creation from the earliest stages, countering the “epistemic injustice” that has historically reserved this privilege to researchers [ 8 ]. One approach, responsive research, seeks first to empower the least empowered stakeholders by providing them a platform to voice their priorities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current emphasis on mental health reform, at least in Australia, also means that it is critical to consider how people with lived-experience may increasingly lead or co-lead co-design processes ( 15 ). That means there is a need to attend to co-analysis and interpretation of the results of co-design so that epistemic injustices (how knowledge is formed, shared, implemented, and evaluated) are not repeated inadvertently ( 5 ). In the shorter term, where co-design is espoused, there is a need for actively attending to how power was re-balanced and where designers were positioned within co-design processes.…”
Section: Introductionmentioning
confidence: 99%